Dolomite-based binders manufactured using concentrated solar energy in a fluidised bed reactor. (15th January 2022) - Marroccoli, Milena; Ibris, Neluta; Telesca, Antonio; Tregambi, Claudio; Solimene, Roberto; Di Lauro, Francesca; Ruiz de Ballesteros, Odda; Salatino, Piero; Montagnaro, Fabio
Highlights: Low-CO2 dolomite-based binders were synthesized. Light burned dolomite was manufactured from solar driven calcination in fluidised bed. Slaked dolomite was mixed with blast furnace slag or coal fly ash samples. Formation of hydrotalcite and calcium silicate hydrates was demonstrated. The proposed approach reduces the carbon footprint of the cement industry. Abstract: Dolomite-based binders are characterised by interesting technical and environmental features. For their synthesis, sources of both CaO and MgO are required. The idea developed in this work is to couple the synthesis of dolomite-based binders, starting from a natural dolomite, through the concept of concentrated solar energy (needed to drive the endothermal dolomite calcination process) in fluidised bed reactors. To this end, a fluidised bed system, where the concentrated solar radiation is mimicked by the use of Xe-lamps (short-arc), has been set up and operated. Natural dolomite (sieved in the 420–590 μm size range) was calcined at a nominal temperature of 850 °C, and bed temperature profiles during solar-driven calcination were investigated. Then, four binders were prepared by mixing slaked dolomite (obtained from the hydration of solar calcined dolomite) with either blast furnace slag or coal fly ash as supplementary cementitious materials. The binders were hydrated for curing times ranging from 7 to 56 days. X-ray fluorescence, X-ray diffraction and combined differential thermal and thermogravimetric analyses were employed as characterisation techniques both to analyse the chemical composition of starting materials and to investigate the evolution of the hydration in the four systems.